Application of nanotechnology to improve the durability of smart textiles in the health sector: A systematic review of the literature - Merino-Ramírez, Praxedes Jeanpierre; Vásquez Espinoza, Juan Manuel (LACCEI, 2025)
This systematic literature review addresses the application of nanotechnology to improve the durability of smart textiles in the healthcare sector. The main objective is to identify how nanotechnology has been used to increase the durability of these textiles. The methodology implemented was quantitative and descriptive based on the systematic analysis of the literature, following the PIOC and PRISMA methods. 72 relevant scientific articles published between 2020 and 2024, in English and Spanish, available in the Scopus database were selected. During the analysis, the main challenges were identified regarding the durability of smart textiles, the nanotechnology techniques used, durability indicators and the areas of the health sector where these improved textiles have been implemented. The results reveal that the integration of nanomaterials in smart textiles can provide advanced properties such as greater resistance to abrasion, UV radiation, chemical agents, as well as self-cleaning microbial characteristics, essential for medical applications.